(untitled) (PRÁXIS EM SAÚDE, 2026)
The search for healthy foods has driven the dairy sector to invest in innovative products, such as yogurts with regional fruits. The objective of this study was to develop whole probiotic yogurt flavored with bacuri and to evaluate its microbiological, physicochemical, and sensory characteristics. Two formulations were produced: F1 whole (Docina® + bacuri) and F2 probiotic (Bio-Rich® + Docina® + bacuri). Microbiological analyses (Salmonella sp., molds, yeasts, and E. coli), physicochemical analyses (pH, soluble solids, titratable acidity), and sensory analyses (acceptability, purchase intention, acceptability index) were performed. Sensory analysis results were evaluated using Student’s t test (p < 0.05). A significant difference was observed only for aroma, with F1 presenting slightly higher mean values for aroma, color, and flavor, while F2 was slightly superior in texture. Both F1 and F2 showed an acceptability index ≥ 70%. Market research indicated a positive purchase intention, highlighting F1. Physicochemical parameters met legal standards, and microbiological conditions were adequate. The potential of bacuri as an innovative ingredient is therefore concluded.